PMMA-modified divinylester/styrene resins: Phase diagrams and morphologies - Schroeder, Walter Fabian (2006)
Binary and ternary experimental cloud-point curves (CPCs) for systems formulated with a low molar mass synthesized divinylester (DVE) resin, styrene (St), and poly(methyl methacrylate) (PMMA) were determined. The CPCs results were analyzed with the Flory-Huggins (F-H) thermodynamic model taking into account the polydispersity of the DVE and PMMA components, to calculate the different binary interaction parameters and their temperature dependences. The St-DVE system is miscible in all the composition range and down to the crystallization temperature of the St; therefore, the interaction parameter expression reported for a higher molar mass DVE was adapted. The interaction parameters obtained were used to calculate the phase diagrams of the St-PMMA and the DVE-PMMA binary systems and that of the St-DVE-PMMA ternary sys-tern at three different temperatures. Quasiternary phase diagrams show liquid-liquid partial miscibility of the StPMMA and DVE-PMMA pairs. At room temperature, the St-DVE-PMMA system is miscible at all compositions. Final morphologies of PMMA-modified cured St-DVE materials were generated by polymerization-induced phase separation (PIPS) mechanism from initial homogeneous mixtures. SEM and TEM micrographs were obtained to analyze the generated final morphologies, which showed a direct correlation with the initial miscibility of the system.